THE APPLICATION OF RAHMAAN LIL ALAMIN VALUES IN ISLAMIC RELIGIOUS EDUCATION AS A PREVENTION OF BULLYING IN THE STATE JUNIOR HIGH SCHOOL 22 PURWOREJO - Wahyu Ika Ramadhani; Rifqi Muntaqo; Mukromin (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This study aims to find out the form of bullying that occurs at SMP Negeri 22 Purworejo, find out the application of the Rahmatan Lil Alamin value by Islamic Religious Education (PAI) teachers in an effort to prevent bullying, and find out the results of the application of the Rahmatan Lil Alamin value to the prevention of bullying in the school. This study uses a descriptive qualitative approach with the type of field research, data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out by data reduction, data presentation and conclusion drawn. The results showed that the most frequent form of bullying at SMP Negeri 22 Purworejo was verbal bullying, such as making fun of parents' names and body shaming, while physical bullying occurred on a lower scale. The application of the values of compassion, tolerance, ukhuwah, empathy, and respect for others has been proven to have a positive impact on student behavior. This is shown by the increase in politeness, caring, and tolerance as well as the decrease in reports of bullying cases in the school environment.